INFLUENCE OF SOWING TIMES ON YIELD OF PEANUT VARIETIES (ARACHIS HYPOGAEA L.) - Yurchenko, S.; Shakaliі, S.; Bahan, A. (Scientific Progress & Innovations, 2022)
The cultivation of a rare crop - cultivated peanut (Arachis hypogaea L.) is gaining popularity in Ukraine today. The expansion of the peanut growing zone requires constant improvement of varietal agricultural techniques, which will ensure high yields, improve the quality of oil and processing of vegetable raw materials, and health safety. The sowing period is one of the agricultural techniques that have a significant impact on the formation of peanut yields. In domestic and foreign literature there is no consensus on the timing of sowing when it is advisable to start sowing. The aim of the study was to develop and improve the elements of cultivation technology, in particular the timing of sowing peanut varieties, which increase yields and quality. Field research was conducted during 2020–2021. The object of research was studied according to the scheme of a two-factor experiment. Factor A – peanut varieties Valencia Ukrainian, Stepnyak, Krasnodarets 14. Factor B – options for sowing dates: May 10, May 20, June 1. Quality assessment by weight of 1000 kernels (g) and yield of mature, condensed kernels (%) depending on sowing dates and peanut varietal characteristics was also performed. On the basis of the established regularities of formation of field germination of seeds and passing of the interphase period of sowing-seedlings on June 1 the best variant on terms of sowing was found out. The reaction of the studied peanut cultivars to different sowing dates was determined. It was found that the yield of peanuts by 18.2 % depended on weather conditions, 40.7 % on the variety, 26.6 % on sowing dates, 2.2 % of other factors and 12.3 % was the interaction of AB factors. To increase the yield of peanuts, it is recommended to sow this plant on May 20. At later sowing dates, a decrease in the mass of 1000 nuclei and the yield of mature ones was observed. In the early stages there is a decrease in yield due to adverse development conditions in the initial stages and a decrease in field germination. However, the plants entered the flowering phase earlier, which allowed more fruits to reach maturity before frost. Among the studied varieties, the Valencia Ukrainian variety stood out in terms of yield and size of kernels.